2014
DOI: 10.1371/journal.pone.0094660
|View full text |Cite
|
Sign up to set email alerts
|

Is Treatment with Trimetazidine Beneficial in Patients with Chronic Heart Failure?

Abstract: BackgroundWhether additional benefit can be achieved with the use of trimetazidine (TMZ) in patients with chronic heart failure (CHF) remains controversial. We therefore performed a meta-analysis of randomized controlled trials (RCTs) to evaluate the effects of TMZ treatment in CHF patients.MethodsWe searched PubMed, EMBASE, and Cochrane databases through October 2013 and included 19 RCTs involving 994 CHF patients who underwent TMZ or placebo treatment. Risk ratio (RR) and weighted mean differences (WMD) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 29 publications
(41 reference statements)
2
34
1
13
Order By: Relevance
“…66 In a meta-analysis of 19 RCTs involving 994 HF patients on treatment with trimetazidine or placebo, trimetazidine However, there were no significant differences in exercise duration and all-cause mortality between patients treated with trimetazidine and placebo. 67 Adverse effects associated with trimetazidine have been minor and mostly gastrointestinal. However, retrospective studies have found an association between long-term use of trimetazidine and Parkinson syndrome, gait disturbances and tremor.…”
Section: Trimetazidine In Heart Failurementioning
confidence: 99%
“…66 In a meta-analysis of 19 RCTs involving 994 HF patients on treatment with trimetazidine or placebo, trimetazidine However, there were no significant differences in exercise duration and all-cause mortality between patients treated with trimetazidine and placebo. 67 Adverse effects associated with trimetazidine have been minor and mostly gastrointestinal. However, retrospective studies have found an association between long-term use of trimetazidine and Parkinson syndrome, gait disturbances and tremor.…”
Section: Trimetazidine In Heart Failurementioning
confidence: 99%
“…При другом мета-анализе, выполненном Zhang, et al [65], с включением данных из 16 РКИ с участием в целом 884 пациентов с СН также было показано, что триметазидин уменьшил частоту госпитализаций по сердечно-сосудистым показаниям у пациентов с СН, однако не повлиял на общую смертность. Тре-тий мета-анализ, проведенный Zhou et Chen [66] с включением данных для 994 пациентов с СН из 19 РКИ, подтвердил уменьшение частоты госпитализа-ций по сердечно-сосудистым показаниям; однако достоверного различия по общей смертности между пациентами, получавшими триметазидин или пла-цебо, выявлено не было.…”
Section: эффективность триметазидина в профилактике сер-дечно-сосудисunclassified
“…It reduces the frequency of anginal episodes and improves exercise performance without affecting haemodynamic parameters [13,14]. Cardioprotection [15][16][17][18] has been demonstrated in both animal models [19,20] and patients, whether with CAD [14,[21][22][23][24] or heart failure [25][26][27][28]. TMZ acts by optimising ATP production directly at the cardiac cell level and opposing ischaemic change [16].…”
Section: Introductionmentioning
confidence: 99%